A horizon scan to inform research priorities on post-wildfire forest restoration and recovery in the western United States - Kelly W. Jones; Kelly W. Jones; Daniel Cadol; Melinda Morgan; Camille Stevens-Rumann; Camille Stevens-Rumann; Diane Agnew; Owen Burney; James Calabaza; Marin E. Chambers; Catrin M. Edgeley; Donald Falk; et al. (Frontiers in Forests and Global Change, 2025)
The frequency, severity, and scale of extreme wildfire events is increasing globally, with certain regions such as the western United States disproportionately impacted. As attention shifts toward understanding how to adapt to and recover from extreme wildfire, there is a need to prioritize where additional research and evidence are needed to inform decision-making. In this paper, we use a horizon-scanning approach to identify key topics that could guide post-wildfire forest restoration and recovery efforts in the western United States over the next few decades. Horizon scanning is a method that uses an iterative and structured expert-elicitation process to identify emerging themes or set research agendas. Experts from across researcher and practitioner organizations identified 12 topics as having the greatest potential impact, and being the most time-sensitive to address, for advancing knowledge on post-wildfire forest restoration and recovery. Five topics fall under the social sciences, including institutional coordination, collaborative governance, pre-fire planning, community engagement and equity, and workforce development; four topics relate to forest management, including seed and seedlings, outplanting strategies, post-fire forest trajectories, and climate-informed reforestation; and three relate to hydrology, including soil erosion mitigation, flood and debris flow mitigation, and post-fire water quantity and quality trajectories. While conducted for the contiguous western United States, this analysis is relevant for other regions where both people and forests are impacted by extreme wildfire events. Addressing these topics has the potential to improve the equity, effectiveness, and efficiency of post-wildfire forest restoration and recovery responses.